Retinoic acid receptors: From molecular mechanisms to cancer therapy. (February 2015) - di Masi, Alessandra; Leboffe, Loris; De Marinis, Elisabetta; Pagano, Francesca; Cicconi, Laura; Rochette-Egly, Cécile; Lo-Coco, Francesco; Ascenzi, Paolo; Nervi, Clara
Abstract: Retinoic acid (RA), the major bioactive metabolite of retinol or vitamin A, induces a spectrum of pleiotropic effects in cell growth and differentiation that are relevant for embryonic development and adult physiology. The RA activity is mediated primarily by members of the retinoic acid receptor (RAR) subfamily, namely RARα, RARβ and RARγ, which belong to the nuclear receptor (NR) superfamily of transcription factors. RARs form heterodimers with members of the retinoid X receptor (RXR) subfamily and act as ligand-regulated transcription factors through binding specific RA response elements (RAREs) located in target genes promoters. RARs also have non-genomic effects and activate kinase signaling pathways, which fine-tune the transcription of the RA target genes. The disruption of RA signaling pathways is thought to underlie the etiology of a number of hematological and non-hematological malignancies, including leukemias, skin cancer, head/neck cancer, lung cancer, breast cancer, ovarian cancer, prostate cancer, renal cell carcinoma, pancreatic cancer, liver cancer, glioblastoma and neuroblastoma. Of note, RA and its derivatives (retinoids) are employed as potential chemotherapeutic or chemopreventive agents because of their differentiation, anti-proliferative, pro-apoptotic, and anti-oxidant effects. In humans, retinoids reverse premalignant epithelial lesions, induce the differentiation of myeloid normal and leukemic cells, and prevent lung, liver, and breast cancer. Here, we provide an overview of the biochemical and molecular mechanisms that regulate the RA and retinoid signaling pathways. Moreover, mechanisms through which deregulation of RA signaling pathways ultimately impact on cancer are examined. Finally, the therapeutic effects of retinoids are reported.